Endoscopic Postoperative Recurrence in Crohn's Disease After Curative Ileocecal Resection with Early Prophylaxis by Anti-TNF, Vedolizumab or Ustekinumab: A Real-World Multicentre European Study. (27th July 2022) - Yanai, Henit; Kagramanova, Anna; Knyazev, Oleg; Sabino, João; Haenen, Shana; Mantzaris, Gerassimos J; Mountaki, Katerina; Armuzzi, Alessandro; Pugliese, Daniela; Furfaro, Federica; Fiorino, Gionata; Drobne, David; et al.
Abstract: Background: Endoscopic-post-operative-recurrence [ePOR] in Crohn's disease [CD] after ileocecal resection [ICR] is a major concern. We aimed to evaluate the effectiveness of early prophylaxis with biologics and to compare anti-tumour necrosis factor [anti-TNF] therapy to vedolizumab [VDZ] and ustekinumab [UST] in a real-world setting. Methods: A retrospective multicentre study of CD-adults after curative ICR on early prophylaxis was undertaken. ePOR was defined as a Rutgeerts score [RS] ≥ i2 or colonic-segmental-SES-CD ≥ 6. Multivariable logistic regression was used to evaluate risk factors, and inverse probability treatment weighting [IPTW] was applied to compare the effectiveness between agents. Results: The study included 297 patients (53.9% males, age at diagnosis 24 years [19–32], age at ICR 34 years [26–43], 18.5% smokers, 27.6% biologic-naïve, 65.7% anti-TNF experienced, 28.6% two or more biologics and 17.2% previous surgery). Overall, 224, 39 and 34 patients received anti-TNF, VDZ or UST, respectively. Patients treated with VDZ and UST were more biologic experienced with higher rates of previous surgery. ePOR rates within 1 year were 41.8%. ePOR rates by treatment groups were: anti-TNF 40.2%, VDZ 33% and UST 61.8%. Risk factors for ePOR at 1 year were: past-infliximab (adjusted odds ratio [adj.OR] = 1.73 [95% confidence interval, CI: 1.01–2.97]), past-adalimumab [adj.OR = 2.32 [95% CI: 1.35-4.01] and surgical aspects. After IPTW, the risk of ePOR within 1 year of VDZ vs anti-TNF or UST vs anti-TNF was comparable (OR = 0.55 [95% CI: 0.25–1.19], OR = 1.86 [95% CI: 0.79–4.38]), respectively. Conclusion: Prevention of ePOR within 1 year after surgery was successful in 60% of patients. Patients treated with VDZ or UST consisted of a more refractory group. After controlling for confounders, no differences in ePOR risk were seen between anti-TNF prophylaxis and other groups.